Project management practices in major university-industry R&D collaboration programs - a case study - Fernandes, Gabriela (2023)
University-industry collaboration (UIC) projects are complex undertakings, that can involve multiple parties or stakeholders. Effective management of UICs can mean the difference between success and failure, in terms of technology transfer and research commercialization. This research paper focuses on the micro-level analysis of UICs and in particular the project management practices that can help major UICs deliver benefits and broader societal impact. PM has been evolving toward more hybrid approaches involving both traditional and agile practices. A conceptualization of a hybrid approach is presented based on a literature review. This conceptualization is then used as a starting point for exploratory empirical research. Participant observation, document analysis, and thirty semi-structured interviews were conducted in a large UIC case study to help identify PM practices and check their relevance. Data analysis led to a framework comprising 29 transversal or must-have practices distributed throughout the project lifecycle and 30 contingent or optional practices, divided into traditional, agile and common. This research extends the existing knowledge on UICs by giving a micro-level perspective on managing UIC projects and providing evidence of the adoption of hybrid approaches to assure the overall governance of significant inter-organizational endeavors. The framework provides a roadmap for future major UIC projects.